2018
DOI: 10.1111/jcmm.13793
|View full text |Cite
|
Sign up to set email alerts
|

PLK1 inhibitor facilitates the suppressing effect of temozolomide on human brain glioma stem cells

Abstract: Glioblastoma is the most frequent and most aggressive brain tumour in adults. Temozolomide is an oral chemotherapy drug and one of the major components of chemotherapy regimens used as a treatment of some brain cancers. We examined the tolerance of stem cells isolated from glioma cell line U87 and U251 to temozolomide (TMZ) and explored the effect of PLK1 (Polo like kinase 1) protein expression on TMZ sensibility. In our results, the inhibitory effects of TMZ on glioma cells U87, U251 and its stem cells were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…CDC20 was usually enriched in CD44+ prostate CSCs [41]. Downregulation of PLK1 protein enhanced the drug-resistance of temozolomide (TMZ) in CD133+ stem-like glioma cell lines, while G2/M arrest was induced significantly [42]. TTK was identified as one of the angiogenic modulators in a robust ESC-based vascular differentiation assay, reducing tumor growth, vascular density, and improving lung carcinoma survival in vivo [43].…”
Section: Discussionmentioning
confidence: 99%
“…CDC20 was usually enriched in CD44+ prostate CSCs [41]. Downregulation of PLK1 protein enhanced the drug-resistance of temozolomide (TMZ) in CD133+ stem-like glioma cell lines, while G2/M arrest was induced significantly [42]. TTK was identified as one of the angiogenic modulators in a robust ESC-based vascular differentiation assay, reducing tumor growth, vascular density, and improving lung carcinoma survival in vivo [43].…”
Section: Discussionmentioning
confidence: 99%
“…Several PLK1 inhibitors are currently in clinical trials as cancer therapeutics . BI2536, one of the PLK1 inhibitors, was found to enhance the inhibition of temozolomide(TMZ) on glioma stem cells; BI 6727, a new generation, highly selective inhibitor of PLK1, resulted in decreased cell proliferation and a marked increase in Diffuse Intrinsic Pontine Glioma cellular apoptosis . These findings are absolutely interesting and demonstrate a potential for clinical use of PLK1 targeted therapy.…”
Section: Discussionmentioning
confidence: 92%
“…Cells were dissociated and seeded in 96-well plates at the density of 2 × 10 4 /well, and siRNA or si-NC was transfected into cells when the cell confluence was approximately 70%. After 24,48,…”
Section: Cell Counting Kit-8 Assaymentioning
confidence: 99%
“…50 Inhibition of PLK1 expression can arrest the cell cycle in the G2/M phase, thereby increasing the effectiveness of chemotherapy drugs. 27,28 Combining a PLK1 inhibitor and chemotherapy drugs has already been reported, and can alleviate the drugresistance of tumor cells. 27 To sensitize glioma to TMZ, we devised a vector that could co-deliver TMZ and siPLK1, and both the in vivo and in vitro experiments showed that the effectiveness of TMZ treatment of glioma improved significantly.…”
Section: Discussionmentioning
confidence: 99%
“…27 Liu et al found that a PLK1 inhibitor combined with TMZ efficiently induced G2/M arrest and suppressed cell proliferation and sphere formation in glioma cells. 28 These findings suggested that a combination treatment comprising TMZ and a PLK1 inhibitor could reverse TMZ resistance efficiently in glioma treatment. However, the clinical application of small-molecule kinase inhibitors is greatly affected by offtarget and toxic effects.…”
Section: Introductionmentioning
confidence: 96%